Conquering academia : transparent experiences of diverse female doctoral students - Richardson, Sonyia (Contemporary perspectives on access, equity, and achievement., 2019)
"Across the country, women are pursuing doctoral degrees at a rate higher than males. While the data indicates that women are now more likely to pursue this advance degree, limited research addresses the real experiences of diverse women who are pursuing a doctoral degree. This book highlights the lived experiences of diverse women who are progressing through a doctoral degree program and the challenges as well as opportunities that they face. These women share unique and transparent experiences of progressing through a doctoral program. Through a narrative approach, Conquering Academia Transparent Stories of Diverse Women Doctoral Students, addresses themes of intersectionality, lived experiences, challenges and opportunities, and adopting an academia mindset. Featured in the Contemporary Perspectives on Access, Equity, and Achievement series, this book shares perspectives of diverse women doctoral students and how their cultural identities assist them with navigating the academic landscape. It also provides insight for current female doctoral students about strategic positioning as a student within the doctoral program and personal necessary transformation in academia. It informs faculty and staff in academia about the experiences of diverse women and how to support their progression and overall retention"--